ENERGY-DEPENDENCE OF SF6 DISSOCIATION BY PULSED CO2-LASER RADIATION - Campbell, J; Hancock, G; Welge, K (1976)
The fractional dissociation,32Γ, of 32SF6 by the output of a pulsed TEA CO2 laser has been found to depend upon Φ, the total integrated laser intensity, as 32Γ ∞ Φm for both the P(20) and P(16) laser lines, where m ≈ 3 in the range 2 < Φ < 7.2 J/cm2 and increases from 3 to ≈ 4 as Φ is reduced from 2 to 0.9 J/cm2. © 1976.